ANALISIS KESALAHAN SISWA KELAS VII TERHADAP KONSEP PERKALIAN BESERTA REKOMENDASI DESAIN PEMBELAJARAN KONSEP PERKALIAN - Nurdiyah Kurniati; Sufyani Prabawanto; Haeruddin Haeruddin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Multiplication is one of the operations of basic arithmetic which has an essential role in learning mathematics. But in fact there are still errors made by students in calculating multiplication operations. Therefore, this study aims to comprehensively identify students' errors in the concept of multiplication and provide recommendation learning designs in instilling or constructing the concept of multiplication. This research is a type of qualitative research with a case study approach. The subjects of this study were 34 students of class VII in one of the junior high schools in Samarinda City, East Kalimantan. The data that has been collected is analyzed through three processes, namely data reduction, data presentation, and drawing conclusions. The results showed that there were still errors made by students in solving multiplication problems, including errors in understanding the concept of multiplication as an addition operation, errors in understanding the concept of multiplication as a combination of addition and multiplication operations, and difficulties in multiplying tens and hundreds operations.